New insights into the enzymatic mechanism of human chitotriosidase (CHIT1) catalytic domain by atomic resolution X‐ray diffraction and hybrid QM/MM. (1st July 2015) - Fadel, Firas; Zhao, Yuguang; Cachau, Raul; Cousido‐Siah, Alexandra; Ruiz, Francesc X.; Harlos, Karl; Howard, Eduardo; Mitschler, Andre; Podjarny, Alberto
<x xml:space="preserve">Abstract</x> Chitotriosidase (CHIT1) is a human chitinase belonging to the highly conserved glycosyl hydrolase family 18 (GH18). GH18 enzymes hydrolyze chitin, an N‐acetylglucosamine polymer synthesized by lower organisms for structural purposes. Recently, CHIT1 has attracted attention owing to its upregulation in immune‐system disorders and as a marker of Gaucher disease. The 39 kDa catalytic domain shows a conserved cluster of three acidic residues, Glu140, Asp138 and Asp136, involved in the hydrolysis reaction. Under an excess concentration of substrate, CHIT1 and other homologues perform an additional activity, transglycosylation. To understand the catalytic mechanism of GH18 chitinases and the dual enzymatic activity, the structure and mechanism of CHIT1 were analyzed in detail. The resolution of the crystals of the catalytic domain was improved from 1.65 Å (PDB entry 1waw) to 0.95–1.10 Å for the apo and pseudo‐apo forms and the complex with chitobiose, allowing the determination of the protonation states within the active site. This information was extended by hybrid quantum mechanics/molecular mechanics (QM/MM) calculations. The results suggest a new mechanism involving changes in the conformation and protonation state of the catalytic triad, as well as a new role for Tyr27, providing new insights into the hydrolysis and transglycosylation activities.